2013
DOI: 10.7567/apex.6.065201
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Electron Wave Packet Dynamics in a Two-Dimensional Nanochannel

Abstract: Classical and quantum dynamics are important limits for the understanding of the transport characteristics of interacting electrons in nanodevices. Here, we apply an intermediate semiclassical approach to investigate the dynamics of two interacting electrons in a planar nanochannel as a function of Coulomb repulsion and electric field. We find that charge is mostly redistributed to the channel edges and that an electric field enhances the particle-like character of electrons. These results may have significant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The set of equations (3.13) is different from the ones obtained with the traditional scalar derivation (see §4.c) as it accounts for both the corrected ray Hamiltonian Ω ( n ) and the geometry of the wave packet’s polarization relations in ray phase space through the Berry curvature. Such a form of ray-tracing equations has already been derived for different purposes such as the study of the time-dependent Schrödinger equation in the adiabatic limit [19], the theory of Bohr–Sommerfeld quantization [37] and semiclassical analyses of wave packet trajectories in slowly perturbed crystals [6,14,40,41], optical lattices [18,42] and ultracold atoms [17]. Formal expressions for first-order corrections to transport equations in multi-component fluid wave problems with inhomogeneous media were proposed by Onuki [22], with concrete applications to shallow-water waves.…”
Section: Berry Curvature In Ray Tracing Of Multi-component Wavesmentioning
confidence: 99%
“…The set of equations (3.13) is different from the ones obtained with the traditional scalar derivation (see §4.c) as it accounts for both the corrected ray Hamiltonian Ω ( n ) and the geometry of the wave packet’s polarization relations in ray phase space through the Berry curvature. Such a form of ray-tracing equations has already been derived for different purposes such as the study of the time-dependent Schrödinger equation in the adiabatic limit [19], the theory of Bohr–Sommerfeld quantization [37] and semiclassical analyses of wave packet trajectories in slowly perturbed crystals [6,14,40,41], optical lattices [18,42] and ultracold atoms [17]. Formal expressions for first-order corrections to transport equations in multi-component fluid wave problems with inhomogeneous media were proposed by Onuki [22], with concrete applications to shallow-water waves.…”
Section: Berry Curvature In Ray Tracing Of Multi-component Wavesmentioning
confidence: 99%
“…Here, we are restricted by computational power. However, we can calculate reliable system sizes and several problems like [22,33,34].…”
Section: Comment On the Practical Usementioning
confidence: 99%
“…However, a previous study, which was carried out with a wave packet picture, showed that with high electric fields the particle nature of the electrons emerges. 8) Because the source-drain bias does not scale as severely as the channel length, 2) the electric field in the channel can be as high as 10 MV cm −1 . All things considered, electrons in a nanoscale channel are in the intermediate region between quantum waves and classical particles.…”
Section: Introductionmentioning
confidence: 99%